Social and economic efficiency of functioning of enterprise trade - Gribovich, Lina; Kovalchuk, Olga (My University, 2014)
Economic and social changes in Ukraine considerably influence the development of trade as a scope, which reflects economic, social and policy objectives of businesses, organizations, public and state. Their proper solution depends on the effective functioning of the economic mechanism of the country, its industries and individual needs of all segments of the population. One of the principal ways of solving these problems is to improve business performance as a result of continuous optimization of the production system businesses and reduce all kinds of expenses.
Keywords: enterprise trade; expenses; economic efficiency; підприємство торгівлі; витрати; економічна ефективність; предприятие торговли; экономическая эффективность; расходы; кафедра ділової іноземної мови та міжнародної комунікації